DESIGN AND ANALYSIS OF PASSIVE AND ACTIVE DAMPER FOR WOOD WORKING MACHINE - Amit Shinde; Dr.Sanjay Zope; Prof. Amol Patil (International Journal of Innovations in Engineering Research and Technology, 2021)
In the various working field, the vibration may cause injurious to human body. Especially, the vibration which is non-uniform, constantly and repeatedly transferred to the human body. This vibration gives serious physical problem to worker hand. Hand-arm vibration is the continuous vibration transmitted from a machine into workers’ hands and arms. It can be caused by operating hand-held power tools, hand-guided equipment, or by holding materials being processed by machines. Multiple studies have shown that regular and frequent exposure to HAV can lead to temporary/permanent adverse health effects, which are most likely to occur when contact with a vibrating machine or work process is a regular and significant part of a person’s job. Hand-arm vibration can cause a range of conditions collectively known as hand-arm vibration syndrome (HAVS), as well as specific diseases. In this paper we reduced the hand vibration by using the damper system to the machine.